Herbal Use among Presurgical Patients in Turkey: A Cross-Sectional Study - Fulya Yilmaz; Hazal Ezgi Çifci (Anesthesiology Research and Practice)
Introduction. For centuries before the advent of modern medicine, traditional medicinal plants were the major agents for primary health care. Their use declined in most developed western countries during the last century’s industrialization and urbanization. But, the last two decades have witnessed a new resurgence of interest in herbal and alternative medicines. Methods. The survey was conducted at the Anaesthesiology and Reanimation Department of Training and Research Hospital of Health and Science University among patients who had undergone elective surgery between January 1st 2016 and April 1st 2016. A questionnaire composed of 15 questions was used. Results. A total 87 (14.5%) patients reported the use of herbal medications. Twenty five patients were taking a single herbal medication and 52 patients were taking more than one. 92.5% of patients do not know the side effects of herbal medications. 35 cases of operation patients were questioned by the physician about herbal use, and 228 cases were not questioned by the physician. Conclusion. Anesthesiologist should be aware of the effects of herbals on body functions and possible herbal-drug interactions to take care of such potentional perioperative complications.